An analysis of entropy generation through a circular duct with different shaped longitudinal fins for laminar flow - Dagtekin, I; Öztop, Hakan Fehmi; Sahim, AZ (Pergamon-Elsevier Science Ltd, 2005)
The present study focuses on the entropy generation analysis in a circular duct with internal longitudinal fins of different shape for laminar flow. Three different fin shapes are chosen for the analysis: Thin, triangular and V-shaped fins. Calculations are performed for various dimensionless lengths and number of fins, dimensionless temperature difference and fin angle for triangular and V-shaped fins. It is found that the number of fins and dimensionless length of the fins for both thin fins and triangular fins, and the fin angle for triangular and V-shaped fins have significant effect on both entropy generation and pumping power. Further, both entropy generation and pumping power also are influenced by dimensionless temperature difference. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: entropy generation; laminar flow; circular duct; longitudinal fins